2013
DOI: 10.1098/rsta.2012.0265
|View full text |Cite
|
Sign up to set email alerts
|

Pushing, pulling and twisting liquid crystal systems: exploring new directions with laser manipulation

Abstract: Optical tweezers are exciting tools with which to explore liquid crystal (LC) systems; the motion of particles held in laser traps through LCs is perhaps the only approach that allows a low Ericksen number regime to be accessed. This offers a new method of studying the microrheology associated with micrometre-sized particles suspended in LC media-and such hybrid systems are of increasing importance as novel soft-matter systems. This paper describes the microrheology experiments that are possible in nematic mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 42 publications
(65 reference statements)
1
12
0
Order By: Relevance
“…[74] In another study, it was reported that LC droplets were used to fabricate micrometer-sized cylinders that rotated in a circularly polarized optical trap to measure the viscosity of composite LC. [33] In the same study, the rotation of the LC microdroplets was used to measure host media such as heavy water. [33] LC is a soft but brilliant material that responds to stimuli by adjusting its chemical and physical properties.…”
Section: Lc Microdroplet As Microactuatormentioning
confidence: 99%
See 2 more Smart Citations
“…[74] In another study, it was reported that LC droplets were used to fabricate micrometer-sized cylinders that rotated in a circularly polarized optical trap to measure the viscosity of composite LC. [33] In the same study, the rotation of the LC microdroplets was used to measure host media such as heavy water. [33] LC is a soft but brilliant material that responds to stimuli by adjusting its chemical and physical properties.…”
Section: Lc Microdroplet As Microactuatormentioning
confidence: 99%
“…[33] In the same study, the rotation of the LC microdroplets was used to measure host media such as heavy water. [33] LC is a soft but brilliant material that responds to stimuli by adjusting its chemical and physical properties. The soft microactuator using an LC microdroplet is more flexible than a solid microactuator.…”
Section: Lc Microdroplet As Microactuatormentioning
confidence: 99%
See 1 more Smart Citation
“…By changing the angle at which the collimated beam enters the objective the focal spot is translated laterally, while changing the incoming beam to slightly diverging or converging translates the focal spot axially. The technique is not limited to just water of course, but can for instance also manipulate liquid crystals [77], as long as there is a gradient in refractive index. To be able to manipulate multiple droplets or particles, multiple individually changeable beam wave fronts are required.…”
Section: Optical Manipulation Techniquesmentioning
confidence: 99%
“…Opening the final session of the conference, Helen Gleeson [12] showed how optical traps can be used to manipulate particles in liquid crystals to perform micro-rheology experiments to provide information about the viscosity coefficient ratios of the liquid crystal material and the trap stiffness. Laser tweezers can also be a tool to manipulate liquid crystal droplets, leading to a range of phenomena, including all-optical switches and opto-mechanical transducers ( figure 7).…”
Section: Optical Tweezers and Liquid Crystalsmentioning
confidence: 99%